135k views
1 vote
Show that cos3x=4cos^3 x-3cos x​

User Bones
by
4.6k points

1 Answer

3 votes

Answer:

cos2x=cox^2 x-1

Explanation:

1.If cosx=0 then equality is established

2.If cosx doesn't equal 0 then:

cos(2x+x)=4cos^3 x-3cos x​

cos2x*cosx-sin2x*sinx=4cos^2 x-3cosx

cos2x-2sin^2 x=4cos^2 x-3

cos2x=2+2cos^2 x-3

cos2x=cox^2 x-1

equality is established

User Thot
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.